Analisis Ekokritik dalam Peran Pandawara Group Tentang Sampah Melalui Media Tiktok - Alghony, Ahmad Bustami (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to analyze ecocriticism in the Pandawara Group's role regarding waste through the social media TikTok. as the main object in this study. Activities carried out by the Pandawara Group provide positive comments from various elements of society who use social media, especially TikTok. This research method uses a qualitative descriptive research method with data analysis techniques in this research, using data collection techniques that involve two interrelated components, namely Ecology and Literature. The results of the research in this study show that the ecological transformation in literary learning carried out by the Pandawara Group has been successful, but the awareness that exists among Indonesian society itself has made the ecological transformation uneven in several parts.